2019
DOI: 10.1039/c9fo01010f
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of trans-2,3,5,4′-tetrahydroxystilbene 2-O-β-d-glucopyranoside on liver fibrosis and renal injury induced by CCl4via down-regulating p-ERK1/2 and p-Smad1/2

Abstract: Both as a food and an herbal plant, Polygonum multiflorum (PM) has long been used in food and prescriptions for several centuries in Southeast Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…The MEK/ERK pathway participates in the regulation of liver injury [ 27 , 28 ] by modulating both cell apoptosis [ 29 ] and autophagy [ 31 ], and interestingly, researchers notice that ASP regulates the MEK/ERK pathway in osteoarthritis chondrocytes [ 26 ], which were validated by our data that DB inactivated the MEK/ERK pathway in the chondrocytes, which were reactivated by co-treating cells with ASP, suggesting that ASP activated the MEK/ERK pathway in DB-treated hepatocytes. In addition, based on the published data [ 26 ], we evidenced that ASP promoted cell autophagy in DB-treated hepatocytes by activating the MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEK/ERK pathway participates in the regulation of liver injury [ 27 , 28 ] by modulating both cell apoptosis [ 29 ] and autophagy [ 31 ], and interestingly, researchers notice that ASP regulates the MEK/ERK pathway in osteoarthritis chondrocytes [ 26 ], which were validated by our data that DB inactivated the MEK/ERK pathway in the chondrocytes, which were reactivated by co-treating cells with ASP, suggesting that ASP activated the MEK/ERK pathway in DB-treated hepatocytes. In addition, based on the published data [ 26 ], we evidenced that ASP promoted cell autophagy in DB-treated hepatocytes by activating the MEK/ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The MEK/ERK signaling pathway is closely associated with liver injury [ 27 , 28 ], which involves in regulating both cell apoptosis [ 29 , 30 ] and autophagy [ 31 ]. For example, Fu et al find that activation of the MEK/ERK pathway ameliorates hypoxic/ischemic-induced bone mesenchymal stem cell apoptosis [ 29 ], and Wang et al evidence that MEK/ERK-induced autophagy contributes to cell survival in IPEC-J2 cells with Ochratoxin A exposure [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed materials and methods used herein are provided in Supplementary Material 1, unless otherwise indicated below. RES and its analogues PTE, oxyresveratrol (ORES), acetyl- trans -resveratrol (ARES), and trans -2,3,5,4′-tetrahydroxystilbene-2- O -glucoside (TSG) (Figure ) were obtained as previously described. , Mouse BV-2 microglial cells (China Center for Type Culture Collection, Wuhan, China) were maintained at 37 °C and a 5% CO 2 atmosphere in Dulbecco’s modified Eagle’s medium (DMEM) added with 10% fetal bovine serum (FBS) and 1% streptomycin–penicillin.…”
Section: Methodsmentioning
confidence: 99%
“…MMPs are involved in the degradation of the extracellular matrix, as well as the processing of growth factors, cytokines, chemokines, adhesion molecules, and several other enzymes [ 30 , 31 ]. Several studies have shown that MMP2 and MMP9 are associated with liver fibrosis and that trans-THSG impeded fibrosis-associated extracellular matrix remodeling by inhibiting the transcription of MMP2 and MMP9 [ 32 , 33 ]. In our study, immunoblotting and IHC for MMP2 and MMP9 was used to investigate hyperlipidemia-induced fibrosis in renal tissue.…”
Section: Discussionmentioning
confidence: 99%